PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN KEMAMPUAN ANALISIS SISWA PADA MATA PELAJARAN SKI - Anjallina, Alfiyatun Nikmah; Gustari, Evelin Diah; M. Syarif; Isro’iyah, Lailatul (STAI Pelabuhan Ratu, 2024)
Education plays a strategic role in developing student potential, but challenges remain in the learning process, especially in Islamic Cultural History (SKI) subjects. This study aims to improve the analytical skills of 10th-grade students at MA Darul Hikam Mojokerto through the Mind Mapping method. The research method used was Classroom Action Research (CAR) with two cycles, involving 7 students. Data collection was conducted through observation, tests, interviews, and documentation. Research results showed a significant increase in students' analytical skills, from an average score of 55.5 in the pre-cycle to 62.8 in the first cycle, and reaching 85.1 in the second cycle. The Mind Mapping method proved effective in helping students identify, connect, and analyze historical concepts more deeply. The study concludes that Mind Mapping can be a very good learning strategy to enhance students' critical and analytical thinking skills.